Increasing Awareness of Medical Laboratory Science through Summer Outreach Programs. - CLARK, LINDSEY (Clinical Laboratory Science)
A common challenge in the medical laboratory science (MLS) profession is that it does not often receive the attention it deserves. In an effort to overcome this issue, increase awareness of MLS as a career, and expand recruitment efforts to high school students, the Department of Laboratory Sciences faculty developed a hands-on laboratory experience to be implemented into existing summer outreach programs on the University of Arkansas for Medical Sciences campus. Participants in the outreach program included 175 high school students fromrural areas of the state. This experience involved participants completing a process of DNA extraction using the Bio-Rad Genes in a Bottle™ Kit and viewing a presentation highlighting the MLS profession, program prerequisites, laboratory career opportunities, and salary outlook. A post-experience survey was given to the participants with a 77% response rate. Results showed the overwhelming majority of participants enjoyed the laboratory activity. A total of 53% of survey participants indicated they did not have knowledge of the MLS profession prior to the activity, with 93% indicating the presentation and activity provided a better understanding of the field. While 24% of respondents indicated they were interested in pursuing a career in laboratory sciences, 48% would consider MLS as a steppingstone into another health care-related field. Implementing a laboratory component into existing summer programs proved to be an effective method for program outreach and recruitment among high school students. The department plans to continue offering this experience for future summer outreach opportunities.